Analisis Strategi Pemasaran Digital Dan Daya Saing Pada Usaha Trhift Berbasis Media Sosial Di Kota Palu - Nurfadilah; Rumambi, ST Fahria; Pamora, Marcela Angelina; Ta’ela, Norce Christanti; Rachmad (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2026)
This research aims to analyze the digital marketing strategy implemented by social media-based thrift businesses in Palu City in an effort to enhance business competitiveness in the creative economy era. The method used in this research is a qualitative approach with a descriptive research type. Data collection was carried out through in-depth interviews with the business owners as the key informants. The research results indicate that thrift business actors in Palu City develop a digital marketing strategy that focuses on utilizing the Instagram, TikTok, and E-commerce platforms to reach a wider target market and create strong interaction with consumers. This strategy includes creating appealing and trendy visual content, conducting interactive live shopping, and optimizing e-commerce features for transaction convenience. Amidst the challenge of the stigma associated with second-hand products and fierce price competition, this digital marketing strategy is proven to create a competitive advantage through product differentiation (curated collections), building a unique brand image, and maintaining customer loyalty by forming an online community. Thus, the applied digital marketing strategy is proven to contribute to increasing the competitiveness of thrift businesses amidst the increasingly competitive fashion industry.